Revolutionizing bioenergy: the microalgae-microbial fuel cell frontier - Adil M., Osman; Abdurahman, Nour Hamid; Noormazlinah, Ahmad (EDP Sciences, 2024)
Microalgae-Microbial Fuel Cell (M-MFC) technology stands out as a highly promising innovation at the nexus of renewable energy and environmental conservation. This cutting-edge approach utilizes microorganisms, including bacteria and algae, to convert the chemical energy in wastewater into electricity, addressing both wastewater treatment and electricity generation. M-MFC relies on microorganisms to convert chemical energy, utilizing components readily available in wastewater, making it a sustainable energy source with considerable potential. Beyond its eco-friendly electricity generation, M-MFC offers cost-effective electricity production, alleviating expenses associated with wastewater treatment and overall electricity consumption. In this comprehensive review, we explore the intricate bio-electrochemical mechanism of M-MFC, shedding light on recent developments and applications. The discussion encompasses crucial factors influencing M-MFC performance, and its essential elements and functions. This review examines the MFC system, particularly M-MFCs, with a focus attention to the functions of key elements such as the anode, cathode, and microorganisms. Additionally, it delves into the material design and configuration of M-MFCs. Furthermore, the review addresses current issues and limitations related to M-MFC systems.